ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN HARGA POKOK KAMAR HOTEL - suprajitno, Dwi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
Calculation of the cost of products at the Hotel Permata still use traditional cost accounting methods. Traditionally, charging for costs not directly done using the basic loading overall or per department. This will cause the resulting product can’t reflect the actual cost is absorbed to produce the products. As a result the product will appear under costing and over costing. Activity Based Costing  System is a method that can overcome the disadvantages of traditional cost accounting system. To overcome the drawbacks of the traditional  costs accounting system, then there is a method activity based costing system is a method of applying the cost of the product by charging fees based on activity. This study has the objective to obtain accurate information on the process approaches Activity Based Costing in generating calculating the cost of the hotel rooms in Hotel Permata in Gombong , so it can be clearly known cost elements involved in the stages of calculating the cost of the room , and to compare the magnitude of the cost of a hotel room , using the traditional cost accounting methods and Activity Based Costing System at Permata Hotel. The cost of the room based on traditional cost accounting systems for rooms Kenanga Rp 83,473.81, room Mawar Rp 125,244.55, room Anggrek B Rp 141,975.59, room Anggrek A Rp 150,203.21 , room Flamboyan B Rp 233,727.34 and the room Flamboyan A Rp 250,282.54. The cost of the room using Activity Based Costing for room Kenanga Rp 89,037.54 , room Mawar Rp 113,183.14, room Anggrek B Rp 143,907.45, room Anggrek A Rp 153,923.35 , room Flamboyan B Rp 236,613.90 , and the room Flamboyan A Rp 264,866.43. In Activity Based Costing System method using the system for calculating the cost of the room, the cost charged to the costs incurred on the basis of product and also use a base of more than one cost driver.   Keywords     : Activity Based Costing, cost of rooms, cost pool, cost driver.